Validity Beyond Measurement: Why Psychometric Validity Is Insufficient for Valid Psychotherapy Research - Truijens, Femke L.; Cornelis, Shana; Desmet, Mattias; De Smet, Melissa M.; Meganck, Reitske (Frontiers in Psychology, 2019)
In psychotherapy research, ‘validity’ is canonically understood as the capacity of a test to measure what is purported to measure. However, we argue that this psychometric understanding of validity prohibits working researchers from considering the validity of their research. Psychotherapy researchers often use measures with a different epistemic goal than test developers intended, for example when a depression symptom measure is used to indicate ‘treatment success’ (cf. outcome measurement for Evidence-Based Treatment). However, the validity of a measure does not cover the validity of its use as operationalization of another target concept within a research procedure, nor the validity of its function towards an epistemic goal. In this paper, we discuss the importance to consider validity of the epistemic process beyond the validity of measures per se, based on an empirical case example from our psychotherapy study (‘SCS’, Cornelis et al., 2017). We discuss why the psychometric understanding of validity is insufficient in covering epistemic validity, and we evaluate to what extent the available terminology regarding validity of research is sufficient for working researchers to accurately consider the validity of their overall epistemic process. As psychotherapy research is meant to offer a sound evidence-base for clinical practice, we argue that it is vital that psychotherapy researchers are able to discuss the validity of the epistemic choices made to serve the clinical goal.